The Effects Of Sukuk (Islamic Bonds) In The Economy - Derry Fahrian; Chenny Seftarita (Proceedings of AICS - Social Sciences, 2016)
This study aimed to analyze the influence of sukuk towards Gross Domestic Product (GDP) in the short term and the long term. The data used in this research is sukuk and Gross Domestic Product (GDP) quarterly data from 2009 until 2015 in the form of time series, processed and analyzed by the method of estimation of Autoregressive Distributed Lag (ARDL). The results of this study indicate that factors influencing the Gross Domestic Product (GDP) in the short term and the long term is the Gross Domestic Product (GDP) and the Sukuk. In the short term Gross Domestic Product (GDP) influencing the Gross Domestic Product (GDP) itself positively and significantly, while Sukuk influencing the Gross Domestic Product (GDP) negatively. In the long term both of Sukuk and Gross Domestic Product (GDP) influence the Gross Domestic Product (GDP) positively and significantly. The study conclude that the increase in funding sources could increase the Gross Domestic Product (GDP) in order to increase economic growth. Thus it is critical to increase the sources of financing to stimulate economic growth in Indonesia.